Isu-Isu Filosofis dalam Pendidikan Menurut George R. Knight - Badani, Abd Quddus al (TSAQOFAH, 2021)
Philosophy is the source of science and technology. Talking about philosophy will certainly never end. The book by George R. Knight which has the original title "Issues and Alternatives in Educational Philosophy" which is the main source in this paper is a survey of philosophy and philosophical issues that are relevant to the education profession. Starting from Knight's concern over the symptoms of "mindlessness" or what can be interpreted as narrow thinking, especially in the world of education. Knight's work became a mandatory book and the main reference in the field of educational philosophy. The philosophy of education will lead educational practitioners to interact directly with the problems that underlie the meaning, purpose of life and education. In this paper, we will focus more on philosophical issues in education. This is considered important because the existing philosophical issues will lead to the educational goals to be achieved.